Growth and convergence in ASEAN: a dynamic panel approach - Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
This study investigates the issues of convergence and economic growth in the ASEAN. Preliminary graphical observations find strong evidence of β and σ convergence after the expansion of ASEAN membership. This results support the convergence theory that poor countries in ASEAN do catch up with the rich ones. The convergence and growth effects in the ASEAN integration is estimated by using the dynamic heterogenous panel approach namely Pooled Mean Group Estimator (PMGE). The empirical evidence supports unconditional and conditional convergence hypotheses in the ASEAN5 namely Indonesia, Malaysia, Singapore, The Philippnes and Thailand, for the 1960-2004 period. The ASEAN5 tends to converge to a steady state growth rate of per capita GDP with a speed of convergence of between 1.6% and 16.6%.